Alternatif Penyelesaian Sengketa dan Peran Etika Profesi Hukum: Meninjau Polemik Pembangunan Jalan Tol Mojokerto–Kertosono Tahun 2016 - Tania Melantika Masita Mally; Mega Dewi Ambarwati (JURNAL ILMIAH NUSANTARA, 2025)
The construction of the Mojokerto-Kertosono toll road has raised many problems for the local community. This ambitious infrastructure project faces various disputes, including land conflicts and compensation issues involving various parties including the government, developers and local communities. This article aims to examine the potential for implementing Alternative Dispute Resolution (APS) in resolving disputes over the construction of the Mojokerto-Kertosono toll road by focusing on the important role of legal professional ethics in the dispute resolution process, highlighting the challenges faced, including conflicts of interest and protecting community rights. Apart from that, it also serves as a basis for ensuring a fair and transparent APS process. This research uses qualitative analysis methods using various data sources, including academic journals, government documents, and related books to collect relevant information.